Prestigious Journals, Predatory Publishers and the Tall Poppy Syndrome in Medicine - Douglas E Garland (Journal of Vaccines and Immunology - Peertechz Publications, 2019)
Fringe medicine (euphemistically called alternative), their articles (sometimes called throw aways) and products (supplements) have peacefully but uncomfortably coexisted with traditional medicine. The advent of the internet and the spread of misinformation have made traditional medicine evaluate its approach on all medical information. Traditional or prestigious journals, not without their own failings, are now in competition with the internet which includes open access e-journals, which have given rise to predatory publishers, as well as medical misinformation. Doctors must determine which articles are trustworthy. A new hybrid article may emerge.